MOTIVATION IMPROVEMENTS AND MATH LEARNING OUTCOMES IN FUNCTION COMPOSITION AND INVERSE FUNCTION MATERIALS THROUGH COURSE REVIEW HORRAY MODEL FOR STUDENTS IN XI IPA 1 OF SMA N 5 MAGELANG ACADEMIC YEAR 2017/2018 INDONESIAN - Siti Zulaichah (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The purposes of this research are to improve the learning outcomes of Mathematics in the function composition for students of XI IPA 1 SMA Negeri 5 Magelang Even Semester Academic Year of 2017/2018 and to figure out to which extent is the learning outcomes improvement. Method used was Class Action Research consisting of 2 cycles, with data analysis applied was comparative descriptive analysis by comparing data between cycles. This research found that Course Review Horray learning model is able to improve the Mathematics learning outcomes in the function composition material for students of XI IPA I SMA Negeri 5 Magelang Even Semester Academic Year of 2017/2018. The increase in the Mathematics learning outcomes is 23.81% in which at the cycle II those who accomplished were 61.90% students became 85.71% at cycle II after applying the Course Review Horray learning model in the function composition for students of XI IPA I SMA Negeri 5 Magelang Even SemesterAcademic Year of 2017/2018.